Analisis Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Produktivitas Tenaga Kerja - Ucik Sinta Nuriya; Nadira Salsabila; Najwa Raisya Salsabila Azzahra; Nurus Sobakh (Indo Publishing, 2026)
This research aims to analyze the role of human resource management in increasing labor productivity. The approach used is qualitative with the literature study method. Data is obtained from various sources such as books, scientific journals, and relevant research articles. The data analysis technique is carried out in a qualitative descriptive manner through the process of studying, comparing, and interpreting theories and previous research results. The results of the study show that human resource management has an important role in increasing labor productivity, especially through the management of the quality of human resources which includes education, skills, work experience, and health conditions. Effective human resource management is able to create a more productive, efficient, and optimally performing workforce. Therefore, the implementation of good human resource management is an important strategy in achieving organizational goals.